Pengaruh Informasi Akuntansi Terhadap Harga Saham Perusahaan - Hutabarat, Wilda Sari; Buulolo, Fince Aswadi; Rajagukguk, Erlin Dermauli; Oktaviani, Ribka; Katharina, Ninta; Seliamang, Yunelci Martha (Gorontalo Accounting Journal, 2023)
The main objective of this study is to test and analyze the influence Current Ratio, Return On Asset, Total Asset Turn Over, and Net Profit Margin to Share Prices in food and beverage sub-sector manufacturing companies The period 2019-2021 both partially and simultaneously. The method used is a quantitative approach with statistical data analysis using multiple linear regression analysis where the data is processed with SPSS 25 software. The research criteria applied were purposive sampling techniques so that the research became 19 samples with observation results obtained 57 research samples. The results of the coefficient of determination analysis show that 17.4% of stock prices are influenced by independent variables, the rest of which are influenced by variables outside the study and simultaneous testing of variables CR, ROA, TATO NPM have a significant effect on stock prices. The test results of the variables current ratio, return on assets and total asset turn over partially cannot affect the stock price significantly but the variable net profit margin can have a significant influence on the stock price.